Anharmonic Effect of the Unimolecular Isomerization/Decomposition of Benzyne. Issue 4 (16th March 2015) - Li, Qian; Yao, Li; Lin, S. H.
Abstract: The anharmonic and harmonic rate constants were calculated for the unimolecular decomposition of o ‐benzyne, the isomerization of o ‐benzyne to m ‐benzyne, the isomerization of m ‐benzyne to p ‐benzyne and unimolecular decomposition of p ‐benzyne by using the Rice–Ramsperger–Kassel–Marcus (RRKM) theory respectively, in the canonical and microcanonical systems. The geometry and the vibrational frequencies were calculated by MP2 and B3LYP methods with 6‐311G(d, p) basis set and the barrier energies were corrected using CBS‐QB3 theory. The anharmonic effect on the reactions was also examined. Comparison of results for the decompositions of benzyne indicate that both in microcanonical and canonical cases, the anharmonic effect on the decomposition of the o‐ C6 H4 and p‐ C6 H4 are significant, while the anharmonic effect on the two isomerizations are not pronounced. Abstract : The anharmonic effects on unimolecular isomerization / decomposition of benzyne were examined. The comparison shows that, both in microcanonical and canonical systems, the anharmonic effects on the decomposition of the o ‐benzyne and p ‐benzyne are significant, while the anharmonic effects on the two isomerizations of o ‐benzyne to m ‐benzyne, m ‐benzyne to p ‐benzyne are not pronounced.